Comportamiento reproductivo y mutilaciones en el cangrejo de las rocas Grapsus grapsus (Linnaeus, 1758) (Crustacea, Decapoda) - Romero, Leonardo (2003)
We have analysed molt frequency and reproductive behaviour of G. grapsus in relation to mutilation frequency and cannibalism observed during mating. Observations and surveys were carried out between December 1990 and December 2001, on a 200 m stretch rocky shore in the south of Ancon Bay, Lima, Peru. Population of G. grapsus was organized in groups of variable numbers around crevices. The courtships behaviour of G. grapsus was based on the «search-interception» process including the defence of semi-permanent territory, along mate-tracking behaviour and interception by several males. A total of 312 copulation events were observed with the highest in summer. Eleven matings ended in death, seven victims of those being males. In this study 8421 molts were collected, 418 had mutilations or injuries in the cephalothorax or abdomen. There was no significant difference in the sizes of mutilated individuals between the two sexes. 73% of mutilated molts had one mutilation (injury), 20% two mutilation and 6% three mutilations and up to seven mutilations were recorded. Frequency of mutilation was significantly higher in males than in females. Mutilated appendices were different between sexes. Chela and second legs were more frequently mutilated in males and the fourth and third legs in females. We propose that mutilations observed were produced during copulation, manly due to size sizes.